Toward Scalable Growth for Single-Crystal Graphene on Polycrystalline Metal Foil - Jang, Hyeon Sik; Lim, Jae Young; Kang, Seog Gyun; Seo, Young Min; Moon, Ji Yoon; Lee, Jae Hyun; Whang, Dongmok (ACS Nano, 2020)
Despite the enormous potential of the single-crystalline two-dimensional (2D) materials for a wide range of future innovations and applications, 2D single-crystals are still suffering in industrialization due to the lack of efficient large-area production methods. In this work, we introduce a general approach for the scalable growth of single-crystalline graphene, which is a representative 2D material, through "transplanting" uniaxially aligned graphene "seedlings" onto a larger-area catalytic growth substrate. By inducing homoepitaxial growth of graphene from the edges of the seeds arrays without additional nucleations, we obtained single-crystalline graphene with an area four times larger than the mother graphene seed substrate. Moreover, the defect-healing process eliminated the inherent defects of seeds, ensuring the reliability and crystallinity of the single-crystalline graphene for industrialization.
Keywords: Catalytic growth; CVD synthesis; Future innovations; Homoepitaxial growth; Polycrystalline metals; Production methods; Single-crystalline; Two Dimensional (2 D); 2D materials; CVD synthesis; graphene; scalable growth; seed; single crystal